In-person and online escape rooms for individual and team-based learning in health professions library instruction. - Helbing, Rachel R.; Lapka, Stefanie; Richdale, Kathryn; Hatfield, Catherine L. (Journal of the Medical Library Association, 2022)
Background: A growing body of research demonstrates that adapting the popular entertainment activity "escape rooms" for educational purposes as an innovative teaching method can improve the learning experience. Escape rooms promote teamwork, encourage analytical thinking, and improve problem solving. Despite the increasing development and use of escape rooms in health sciences programs and academic libraries, there is little literature on the use of this method in health sciences libraries with health professions students. Case Presentation: Staff at a health sciences library collaborated with faculty to incorporate escape rooms into library instruction in a variety of settings (in-person, hybrid, online) and formats (team, individual) with health professions students from various disciplines (optometry, pharmacy, medicine). The escape rooms described in this paper offered unique experiences for students through active learning. Discussion: Important considerations when planning escape rooms for health sciences library instruction include deciding on team-based or individual design, calculating potential costs in time and money, deciding on an in-person, hybrid, or online format, and determining whether grades should be assigned. Escape rooms can be an effective strategy for library instruction in the health sciences, working in multiple formats to bring game-based learning to a variety of health professions students.